Sociodemographic Characteristics and Forensic Evidence of Sexual Assault Victims - Abdul Samad, Aisha Khalid, Shahla Imran, Naseem Akhter, Ishrat Bibi, Ramlah Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate sociodemographic characteristics and forensic evidence of sexual assault victims. Study Design: Retrospective study. Place and Duration of Study: Medicolegal section of Peoples Medical College Hospital (PMCH) and Department of Forensic Medicine & Toxicology, Peoples University of Medical & Health Sciences, Nawabshah District Shaheed Benazirabad from 1st January 2019 to 31st December 2021. Methodology: One hundred and forty female victims of sexual assaults were enrolled. Results: The reports of sexual assaults were higher in females of 15-25 years age group (55.71%) as compared to the age group of 26-35 years (34.29%). With reference to marital status, occupation, and socio-economic class, most of the females were unmarried (66.43%), nonworking (44.29%), and from the lower class (65.71%). A discrepancy was found between positive penetration history (72.14%) and positive laboratory findings (43.57%) which could be attributed to reporting of a sufficient number of sexual assaults after 48 hours (37.86%). Conclusion: The women of younger age (15-25 years) and having low access to paid employment were more prone to sexual assaults. The time-lapse between the occurrence of incidence and collection of forensic evidence could impact the agreement between penetration history and laboratory analysis. Keywords: Sociodemographic, Forensic evidence, Sexual assault victim